Femmes des "Mille et une nuits" - Garcin, Jean-Claude (Arabica, 2016)
We can assume that we find for the first time in the 15th century the character of Šahrazād as a courageous woman who had taken upon herself to get the king away from his bias against the women after his wife deceived him. Šahrazād tells him stories in which women have not infrequently more fortitude and deserve more to be trusted than men who are sometimes immature. But there are also from the same century other stories in which ancient themes continue, for instance about crafty and lustful women. In the 16th century, “Dalila the wily” upgrade crafty women, but in the seventeeth century, the Ottoman’s connections with Protestant communities in Germany introduced to the Arabian Nights European witches and bird-women. Anyway men have to avoid to fall in love with women. During the 18th century, a solution to the problem of good relationship between men and women is sketched in the “Masrūr and Zayn al-Mawāṣif” story. The two characters, a christian man and a jewish woman, live happily after they had both converted to Islam. In the same way, the Arabian Nights end when the king gives up his bias against the women and marry Šahrazād, “a good wife [. . .] a pure, a chaste, a devout one”. But he has to keep faith with his wife and preserve responbility for her, according to Islamic Law.